Analysis Factor Affecting The Use Of Digital Payment With The Extended Utaut Model - Alien Arianita; izar Alfansi; Sularsih Anggarawati (UNIB Press, 2023)
This Study aims to determine the factors that influence users in using digital payment in transactions. The Unified Theory of Acceptance and Use of Technology (UTAUT) is used as a research model with independent variables: performance expectations,effort expectancy, facility conditions, social influence and extend UTAUT research model with trust and perceived innovativeness. This study also changes the relationship between the influence of intention to use E-WOM and Loyalty.This research method uses an online survey method that is distributed using Google Surveys. The research data were collected from 355 digital payment users of Indonesia private banks who had the experience of using digital payment. The structural equation modeling technique was used to test the research hypotheses. Primary data collected were analyzed using SmartPLS software. Findings suggest that performance expectancy, facilitating conditions, trust, perceived innovativeness factor in influencing the digital payment adoption intention. effort expectancy, social influence, do not have a effect on behavioral intentions. On the other hand, digital payment adoption intention has also had a significant positive effect on loyalty and word-of-mouth (WOM). This study contributes to the literature on digital payment services and usage behavior. This research can provide an overview for banking and non-bank financial services to always maintain the quality of digital payment applications so that they always provide benefits to improve performance, effectiveness and also productivity for those who use them. And innovate and also develop new features in digital payment applications in order to attract public attention. From theoretical and managerial aspects, this study has particular value for the literature on digital payment intention in general and banking in particular. The present study provides a conceptual framework for digital payment M-banking adoption intention, which could be used in digital services. In addition, this study sought to extend UTAUT and to examine the behavior intention in WOM and Loyalty. Keywords: Digital Payment, WOM, Loyalty, UTAUT, behavior intention , digital payment adoption Paper type Research paper